An integrative approach reveals a new species of Zoantharia (Cnidaria, Anthozoa), Terrazoanthus silveirai, in the South-western Atlantic Ocean. Issue 7 (14th September 2021) - Vaga, Claudia F.; Migotto, Alvaro E.; Santos, Maria E. A.; Honji, Renato M.; Reimer, James; Kitahara, Marcelo V.
ABSTRACT: The recently erected macrocnemic family Hydrozoanthidae comprises relatively few species recorded from tropical and subtropical regions. In the Atlantic Ocean, this family has been reported only from three locations: the Caribbean Sea, the Argentine continental shelf and the Cape Verde Islands. Based on a study of colonies collected during scuba diving at Alcatrazes Archipelago's main island (São Paulo State), south-eastern Brazil, a new species belonging to the genus Terrazoanthus is described as T. silveirai sp. nov. Vaga, Migotto & Kitahara. Morphological and ecological observations coupled with molecular analyses revealed a unique cnidome, a novel facultative association with sponges, and confirmed the phylogenetic position of this new species within Hydrozoanthidae. Our results represent the second record of Hydrozoanthidae and Terrazoanthus from the South-western Atlantic, expanding the sparse taxonomic knowledge of the order Zoantharia in this area. http://zoobank.org/3969190B-A039-457C-8101-44FEF60B4D43